A Systematic Review and Meta-Analysis on the Role of Somatostatin Therapy in Non-Variceal Gastrointestinal Bleeding - Magnus Chun; Tahne Vongsavath; Sneh Sonaiya; Lily Liu; Kyaw Min Tun; Kavita Batra; Robert G. Gish (Gastroenterology Insights)
Background and Aims: Non-variceal upper gastrointestinal bleeding (NVUGIB) is a common cause of hospitalizations, with proton pump inhibitors (PPIs) being the mainstay treatment. However, there is a lack of high-level evidence to show if adjunctive medical therapy (somatostatin and its analogs) can improve outcomes. This systematic review and meta-analysis aim to evaluate the outcomes of PPIs with adjunctive therapy versus PPI monotherapy in treating NVUGIB in an in-patient setting. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, major databases were systematically searched to retrieve English-only, original studies, published from 1 January 2000 to 31 December 2023, investigating NVUGIB only. The primary outcomes included the mortality rate within 7 days of therapy, rebleeding rate within 7 days of therapy, and length of hospital stay. Results: Seven studies with 789 patients had a pooled mortality rate of 2.0% (95% CI, 0–4.0%), and the pooled risk ratio was 1.11 (95% CI, 0.50–2.48; p = 0.79) between PPI monotherapy and PPIs with adjunctive medical therapy. The pooled rebleeding rate was 13% (95% CI, 6–20%) and the risk ratio was 1.04 (95% CI, 0.73–1.48; p = 0.83). The pooled average length of stay in the hospital was 5.47 days (95% CI, 3.72–7.21 days), with insignificant weighted differences between the two groups. No statistically significant differences were noted in surgical management risk ratios or amount of blood transfusion. Conclusions: Among patients with NVUGIB, adjunctive medical therapy offered no clinical benefits given the statistically insignificant differences in the primary outcomes. However, this conclusion is limited by the considerable variability in treatment protocols, weak control of confounding variables, and missing clinical information in the original studies. Therefore, better-quality, large-scale randomized controlled trials are needed, ideally using standardized somatostatin dosing, timing, delivery routes, and clearly defined inclusion criteria to more accurately evaluate the role of somatostatin in NVUGIB management.